UNIMAS E-Balik Management System - Sivavikkraman, Puvanamala; Johari, Abdullah (Faculty of Computer Science and Information Technology, 2015)
Security is of crucial importance to any organization especially when dealing with the safety of students. Likewise, UNIMAS gives a lot of attention to the safety of the students especially during the curfew hour although the university management is quite lenient and allows the students to exit and enter the university vicinity during the curfew hours. However, these students are required to write down their particulars at the guard post. Many students take advantage of this situation and falsify their data as there is no proper way of validating the student’s data. Thus, a web-based system is proposed to scan the student’s matric card using a barcode scanner to allow true data to be submitted to the database so that college principals and the system administrator can easily access these names anytime and anywhere.